Focused low-intensity pulsed ultrasound upregulates Vimentin protein expression to inhibit chondrocyte apoptosis - LI Dongqian; YE Haixia; YU Lehua; JIA Lang (陆军军医大学学报, 2023)
Objective To investigate the molecular mechanism of focused low-intensity pulsed ultrasound (FLIPUS) to inhibit chondrocyte apoptosis through mechanical effects. Methods Primary chondrocytes were isolated from the knee of suckling C57BL/6J mice with trypsin combined with type Ⅱ collagenase and then cultured with IL-1β stimulation to mimic a cellular model of osteoarthritis-like chondrocyte injury. The model was validated and related protein expression changes were detected after different treatment times. The cells were divided into Control group, IL-1β group and IL-1β+FLIPUS group. The apoptotic rate of chondrocytes was detected by flow cytometry, structural distribution of Vimentin was observed with immunofluorescence assay, and expression of Col2α1, MMP13, Bcl-2, Vimentin and p-Tyr397 was measured with Western blotting. Results Primary mouse chondrocytes were isolated and cultured, and simulated to be a cellular model of osteoarthritis-like chondrocyte injury. With elapse of IL-1β treatment time, the protein levels of Col2α1, Vimentin, p-Tyr397, Bcl-2 and p-AKT were decreased (P < 0.05), and those of MMP13, Bax and cleaved-Caspase3 were increased (P < 0.05) compared to the levels in the Control group. FLIPUS led to reduced apoptosis (P < 0.001), decreased MMP13 expression (P < 0.05) and enhanced levels of Col2α1 (P < 0.01), and Bcl-2 and Vimentin and p-Tyr397 (P < 0.05) when compared with the IL-1β group. Vimentin distribution was remodeled, with increased fluorescence intensity. Conclusion FLIPUS up-regulates Vimentin expression, promotes phosphorylation at the Tyr397 locus of FAK, and inhibits apoptosis in chondrocyte.